HUBUNGAN KEPEMIMPINAN, MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Pandapotan, Frans David; Tampubolon, Emma; Hutapea, Ganda T (Universitas Kristen Indonesia, 2016)
The purpose of this study was to determine the relationship work motivation and employee performance, relationship with the leadership performance of employees of PT. Sari Coffee Indonesia. This research was descriptive - correlation with a sample of 30 employees and the data were analyzed using the Spearman rank correlation analysis. The results of this study indicate that (1) Based on the results of Spearman correlation test above can be seen significant value of 0.000 <0.05, it can be concluded that there is a significant relationship between the variables of leadership performance, while the value of Spearman correlation between leadership and performance of 0.667 which is positive and signifies the strong relationship, it means there is a positive relationship that is if the leadership increases, the performance will increase, and vice versa. (2) Based on the results of Spearman correlation test above can be seen significant value of 0.000 <0.05, it can be concluded that there is a significant relationship between the variables of motivation to performance, while the value of Spearman correlation between motivation and performance of 0.714 which is positive and indicates a great relationship strong, it means there is a positive relationship that if the motivation increases, the performance will increase, and vice versa.Keyword leadership, work motivation and employee performance.